Rotavirus vaccination and the risk of type 1 diabetes and celiac disease: A systematic review and meta-analysis - Zhang, Xue; Xu, Xiang-fei; Jin, Jie (Frontiers in Pediatrics, 2022)
Background: Rotavirus vaccination has been proven to effectively protect against rotavirus gastroenteritis. However, there are concerns about the relationship between rotavirus vaccination and the risk of autoimmune disorders. Therefore, we performed a systematic review and meta-analysis to comprehensively evaluate the relationship between rotavirus vaccination and type 1 diabetes (T1D) or celiac disease (CD) risk. Methods: A systematic review and meta-analysis were performed to evaluate the type 1 diabetes or celiac disease associated with rotavirus vaccination. The PubMed, Embase, and Cochrane Library databases were searched to identify potential studies for inclusion. Results: Seven articles involving more than 5,793,055 children were included. Our results showed that rotavirus vaccination does not alter the subsequent risk of T1D (RR 0.94, 95% CI: 0.82-1.09) or CD (RR 0.86, 95% CI: 0.64–1.17) after vaccination. Furthermore, the risk of T1D was not increased or decreased for children fully exposed to rotavirus vaccination (RR 0.86, 95% CI, 0.54-1.36) and for children partially exposed to rotavirus vaccination (RR 1.05,95% CI, 0.87-1.26). Conclusion: The findings of this study suggest that rotavirus vaccination does not appear to be associated withT1D or CD in children.